Technological Changes and Challenges in Power Electronics - Adarsh, K. N. (Indian Journal of Power and River Valley Development, 2020)
In earlier days, Mercury Arc Rectifiers were used to convert AC into DC for various applications, be it to charge a battery or to drive a motor. The size of these systems was large, inefficient and dangerous which led the researchers to develop much better devices. Their efforts led to the development of solid state devices like Mosfet, SiC, GaN, IGBT, SCR, GTO etc.